Prognostic value of endometrial thickness in predicting pregnancy onset in IVF cycles: Insights from the “Ansagan Sabi” state program in Kazakhstan - Moshkalova, Gaukhar; Kurmanova , Almagul; Mamedalieva, Nagima; Aimbetova , Aliya; Salimbayeva , Damilya; Kurmanova , Gaukhar; Anartayeva , Gaini; Aripova , Radha; Karibayeva, Indira (Acta Biomedica Atenei Parmensis, 2024)
Background: The introduction of the "Ansagan Sabi" program has expanded access to infertility treatment to patients in Kazakhstan. Endometrial thickness is a crucial factor in determining endometrial receptivity and, consequently, the success of in vitro fertilization (IVF) procedures. Our study seeks to assess the prognostic value of endometrial thickness as a predictor of pregnancy onset in patients undergoing fresh IVF cycles as part of the implementation of the “Ansagan Sabi” state program.Methods: A retrospective analysis was conducted on 279 women who underwent IVF fresh cycle procedures and were recruited under the "Ansagan Sabi" program. Strict selection criteria were applied during the outpatient stage. Demographic and clinical data, including endometrial thickness, were collected for analysis.Results: The analysis revealed that endometrial thickness significantly influenced the likelihood of pregnancy onset, as assessed by logistic regression analysis. Patients with endometrial thickness below 5 mm (Group 1) and between 5 and 7 mm (Group 2) exhibited decreased odds of pregnancy onset compared to those with thicknesses equal to or greater than 7 mm (Group 3).Conclusion: Optimal endometrial thickness, indicated by thicknesses equal to or greater than 7 mm, was associated with improved pregnancy outcomes. The study findings have implications for patient management strategies within the "Ansagan Sabi" program and underscore the importance of optimizing endometrial conditions to enhance IVF success rates. Further research incorporating larger sample sizes and multicenter studies is warranted to validate the findings and explore additional prognostic factors.